Moral Standards for Research in Developing Countries From “Reasonable Availability” to “Fair Benefits” (The Hastings Center report, 2004)
Commentators have argued that when research conducted in a developing country shows an intervention to be effective, the intervention must be made “reasonably available” to the host population after the trial. But this standard is sometimes too stringent, and sometimes too lenient. It offers a benefit, but not necessarily a fair benefit.